The Dynamics of Tobacco Commodity Governance on Farmer Welfare and Economic Resilience in the Temanggung Region - Veni Aprisal; Putri Wulan Nahri; Ristya Rahma Azzahra (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Tobacco commodity management remains a serious issue, particularly in production centers such as Temanggung Regency. This study aims to examine in depth the dynamics of tobacco commodity management in Temanggung Regency and its implications for farmer welfare and regional economic resilience. This study employs a qualitative descriptive approach using literature review methods. The findings reveal that the tobacco trade is dominated by middlemen and factories, leaving farmers in the weakest position. The practice of high-interest debt, known as the nglimolasi system, structurally binds farmers and strips them of control over prices. Conversely, the increase in tobacco excise taxes in 2024, which generated national revenue of Rp216.9 trillion, did not provide protection for farmers. Meanwhile, the allocation of Rp16 billion from the DBHCHT in Temanggung was primarily absorbed by physical programs rather than capacity-building initiatives for farmers. The tobacco industry plays a crucial role in Temanggung's economy, contributing 22.47% to the regional GDP. The vulnerability of this industry directly impacts the region's economic resilience, with social and economic pressures intensifying as farmers' well-being declines.